Assessment of the interleukin 1 gene cluster and other candidate gene polymorphisms in host susceptibility to tuberculosis. - Bellamy, R; Ruwende, C; Corrah, T; McAdam, K; Whittle, H; Hill, A (1998)
SETTING: A study of tuberculosis cases and healthy blood donor controls from the Western Region of The Gambia, West Africa. OBJECTIVE: To investigate the potential role of candidate gene polymorphisms in host susceptibility to tuberculosis. DESIGN: Single base change polymorphisms in interleukin 1 beta (IL1 beta), interleukin 10 (IL10) and fucosyltransferase-2 (FUT-2), microsatellite polymorphisms in interleukin 1 alpha (IL1 alpha) and IL10 and a minisatellite polymorphism in interleukin 1 receptor antagonist (IL1RA) were typed in over 400 tuberculosis cases and 400 healthy blood donor controls. RESULTS: IL1 gene cluster polymorphisms (IL1RA and possibly IL1 alpha) showed marginally significant association with tuberculosis. In particular IL1RA allele 2 heterozygotes were less frequent among tuberculosis cases than controls (P = 0.03). IL1 beta, IL10 and FUT-2 polymorphisms were not associated with tuberculosis. CONCLUSION: Genetic susceptibility to tuberculosis among Gambians may be partly determined by genes in the IL1 gene cluster on chromosome 2. Further association studies will be required on other population groups to confirm whether these results are of biological significance.